Stylosanthes (Leguminosae-Papilionoideae-Dalbergieae) in Northeast Brazil - da Silva Ferreira, Jamile Jorge [UNESP]; Perez, Ana Paula Fortuna [UNESP]; Lewis, Gwilym Peter; Silva, Juliana Santos (FapUNIFESP (SciELO), 2022)
Stylosanthes, with approximately 50 species, is a pantropical, economically important genus of Leguminosae, with several species having forage potential and soil improvement potential. Thirty-two species have been recorded in Brazil, with the Northeast region being one of the main centers of diversity of the genus in the country. Despite this, no taxonomic work focusing on Stylosanthes has been done for the region. This study presents a taxonomic treatment of Stylosanthes species occurring in the Northeast region of Brazil. Botanical specimens were collected in the field together with visits to the main herbaria in the Northeast (ALCB, HUEFS, HUNEB, HVASF) for specimen analysis. Online consultation of databases in virtual herbaria, analysis of regional flora accounts, assessment of types and discussions with legume experts were also undertaken. Twenty-three taxa were confirmed as occurring in NE Brazil, with six new occurrences recorded for the states of Ceará, Paraíba, Piauí, and Rio Grande do Norte. Species in the studied area are mainly differentiated by their fruit and bract morphology.
Keywords: campos rupestres; Cerrado; Fabaceae; flora; plant taxonomy; semiarid